Ethylene-alpha-olefin random copolymer as well as preparation method and application thereof
By developing a specific ethylene-α-olefin random copolymer that contains only components of a specific effluent temperature range during the gradient heating rinsing process, the existing copolymers are solved for insufficient heat resistance and mechanical properties in photovoltaic adhesive films, and improved crosslinking and electrical insulation performance are achieved, which improves the sealing performance and service life of photovoltaic adhesive films.
Patent Information
- Application Number
- CN202411992769.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing ethylene-α-olefin random copolymers have problems such as low heat resistance and insufficient mechanical properties in photovoltaic film applications, resulting in reduced sealing performance and affecting the service life of the components and power generation efficiency.
A random copolymer of ethylene-α-olefin is developed, which only contains two components with a effluent temperature range of 25-40°C and 45-120°C. The proportion of effluent components in the low temperature range is low. The fraction is performed through the gradient temperature-raising effluent process to improve cross-linking and electrical insulation properties.
The copolymer has improved crosslinking speed and anti-induced potential attenuation (PID) performance, and is suitable for photovoltaic film field, improving sealing performance and service life.
Smart Images

Figure CN119775468A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of olefin polymerization, and specifically relates to an olefin copolymer, in particular to an ethylene-alpha-olefin random copolymer, and further discloses a preparation method and application thereof. Background Art
[0002] Polyolefin elastomer (POE) is the product with the smallest specific gravity among polymer materials. It has the characteristics of low cost, light specific gravity, and easy molding and processing. It is widely used in many fields such as industry, agriculture, military, and medicine. Polyethylene is a very important product in the polyolefin industry. It is the largest variety of general synthetic resins. The copolymer obtained by copolymerization of ethylene and α-olefin has the plasticity of plastics and the high elasticity of rubber. It is one of the main directions of the development of high-end polyolefin materials.
[0003] Random copolymers of ethylene and α-olefins are semi-crystalline polymers with an ethylene monomer content of usually more than 55wt% and an α-olefin content of less than 45wt%. Although the random insertion of α-olefins into the ethylene methylene chain structure will destroy the regularity of the polymer chain, reduce the polymer crystallinity, and increase the corresponding light transmittance; however, since the polymer chain structure is composed of non-polar C and H atoms and has very few unsaturated double bonds, random copolymers of ethylene and α-olefins have excellent insulation, water vapor barrier, weather resistance and UV aging resistance, and are widely used in the field of photovoltaic films.
[0004] However, despite the excellent comprehensive performance of POE in photovoltaic film applications, due to the characteristics of semi-crystalline, random copolymer elastomer materials, its own heat resistance is not high and its mechanical properties are insufficient. It cannot be used directly and for a long time in the natural environment where photovoltaic modules are located. Otherwise, even if POE itself has excellent electrical insulation and water vapor barrier properties, its insufficient mechanical properties will still lead to reduced sealing performance, which will naturally lead to the invasion of water vapor into photovoltaic modules, thereby causing the attenuation of electric potential, affecting the service life of the modules and power generation efficiency. It is precisely due to the above reasons that POE must usually be cross-linked when used in the field of photovoltaic films, so as to take into account its excellent insulation, transparency, weather resistance, mechanical strength and sealing. In addition, in the process of photovoltaic film processing, POE is directly cross-linked and formed with solar cells and glass through the addition of cross-linking agents and heating cross-linking processes during the lamination and bonding process with the modules after film formation. However, due to the influence of the non-polar composition of POE itself, the compatibility between the polar component cross-linking agent and POE is usually very poor, which affects the processing efficiency, sealing performance and anti-induced potential decay (PID) performance of POE in the application process of photovoltaic film.
[0005] Therefore, the art expects to develop an olefin copolymer with improved cross-linking and anti-induced potential decay (PID) performance, which is of great significance for the development and promotion of packaging materials in the photovoltaic field. Summary of the invention
[0006] To this end, the technical problem to be solved by the present invention is to provide an ethylene-α-olefin random copolymer, wherein the copolymer contains only two components with elution temperature ranges of 25 to 40° C. and 45 to 120° C., and the proportion of the elution component in the low temperature range is low, the polymer composition is uniform, the copolymer has improved cross-linking and electrical insulation properties, and has the advantages of fast cross-linking speed and excellent anti-induced potential decay (PID) performance in the field of photovoltaic film applications;
[0007] The second technical problem to be solved by the present invention is to provide a preparation method and application of the above-mentioned ethylene-α-olefin random copolymer.
[0008] In order to solve the above technical problems, the present invention provides an ethylene-α-olefin random copolymer, wherein the ethylene-α-olefin random copolymer comprises:
[0009] (1) a soluble fraction having an elution temperature range of 25 to 40°C during a gradient elution with 1,2,4-trichlorobenzene; and
[0010] (2) a soluble fraction having an elution temperature range of 45 to 120°C during a gradient elution with 1,2,4-trichlorobenzene;
[0011] The mass proportion of the soluble fraction at 25-40° C. is 0.5-5wt%.
[0012] Specifically, the ethylene-α-olefin random copolymer, the polymerization raw materials of the ethylene-α-olefin random copolymer include α-olefin monomers and ethylene monomers; wherein,
[0013] The mass content of the α-olefin monomer based on the ethylene-α-olefin random copolymer is 20 to 45 wt%;
[0014] The mass content of the ethylene monomer based on the ethylene-α-olefin random copolymer is 55 to 80 wt%;
[0015] Preferably, the α-olefin monomer includes an α-olefin having 3 to 8 carbon atoms, and preferably the α-olefin monomer includes at least one of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene or 1-octene.
[0016] Specifically, the ethylene-α-olefin random copolymer has a melt flow rate of 0.5 to 30 g / 10 min (2.16 kg, 190° C.) and a density of 0.860 to 0.910 g / cm 3 .
[0017] The invention also discloses a method for preparing the ethylene-alpha-olefin random copolymer, comprising the steps of subjecting ethylene monomer, alpha-olefin monomer, impurity remover, dispersant and polymerization catalyst to polymerization reaction.
[0018] Specifically, the preparation method of the ethylene-α-olefin random copolymer is:
[0019] The amount of the ethylene monomer added is 5 to 20 wt % based on the total amount of the raw material feed of the ethylene-α-olefin random copolymer; and / or,
[0020] The amount of the α-olefin monomer added is 10 to 35 wt % based on the total amount of raw material feed of the ethylene-α-olefin random copolymer; and / or,
[0021] The impurity remover comprises at least one of alkyl aluminum or alkyl aluminoxane; preferably at least one of alkyl aluminum, methyl aluminoxane or modified methyl aluminoxane; preferably triisobutyl aluminum or n-octyl modified methyl aluminoxane; preferably, the amount of the impurity remover added is 5 to 90 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer; and / or,
[0022] The dispersant comprises at least one of C6-C10 aliphatic hydrocarbons, such as one or more of C6-C10 straight-chain alkanes, C6-C10 isoalkanes, and C6-C10 cycloalkanes, preferably at least one of C6, C7, C8, C9 or C10 isoalkanes, for example, one or more of n-hexane, cyclohexane, methylcyclohexane, n-heptane, isoheptane, n-octane, isooctane, n-decane, toluene and xylene; preferably, the dispersant is added in an amount of 55-80 wt % based on the total amount of the raw material feed of the ethylene-α-olefin random copolymer; and / or,
[0023] The polymerization catalyst comprises a main catalyst and a co-catalyst;
[0024] Preferably, the main catalyst comprises a transition metal compound of Group IVB-IIB, preferably bis(methylcyclopentadiene)zirconium dichloride, bis(cyclopentadiene)dimethyl zirconium, disylbis(2-methylindenyl)zirconium dichloride, disylbis(N-tert-butylamino)(cyclopentadienyl)titanium dichloride, disylbis(N-tert-butylamino)(tetramethylcyclopentadienyl)titanium dimethyl, disylbis(N-tert-butylamino)(2,7-di-tert-butylfluorenyl)titanium dichloride, disylbis(N-tert-butylamino)(3-pyrrolylindenyl)titanium dichloride, dibenzhydryl(cyclopentadienyl)(9-fluorenyl)zirconium dichloride, dibenzhydryl(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)titanium dichloride, one or more of dimethyl tert-butyl fluorenyl) zirconium dichloride, dimethylbenzhydryl (cyclopentadienyl) (dibenzofluorenyl) zirconium dichloride, dimethylbenzhydryl (cyclopentadienyl) (2-dimethylamino-fluorenyl) zirconium dichloride, dimethylbenzhydryl (cyclopentadienyl) (octamethyl octahydrobenzofluorenyl) zirconium dichloride, bis (tetramethylcyclopentadienyl) hafnium dichloride, disilyl (9-fluorenyl) (3-tert-butylcyclopentadienyl) hafnium dichloride, diphenylsilyl (9-fluorenyl) (3-tert-butylcyclopentadienyl) hafnium dichloride; based on the total amount of raw material feed of the ethylene-α-olefin random copolymer, the addition amount of the main catalyst is 0.3-5ppm; and / or,
[0025] Preferably, the co-catalyst comprises a fluorine-containing borane or a fluorine-containing borate; preferably one or more of tripentafluorophenyl borane, triphenylcarbon tetrakis(pentafluorophenyl)borate, and N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate; preferably, the co-catalyst is added in an amount of 0.5 to 7 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer.
[0026] Specifically, in the method for preparing the ethylene-α-olefin random copolymer, the reaction temperature of the polymerization reaction is 120 to 220° C., the reaction pressure is 3 to 10 MPa, and the reaction time is 2 to 20 min;
[0027] Preferably, the polymerization reaction comprises the step of continuously introducing the selected reaction materials into a polymerization reactor; preferably, the polymerization reactor is a stirred tank reactor or a tubular reactor with a circulation pump.
[0028] Specifically, the method for preparing the ethylene-α-olefin random copolymer further comprises the step of premixing the ethylene monomer, α-olefin monomer, impurity remover and dispersant before the polymerization reaction;
[0029] Preferably, the temperature of the premixing step is -10 to 150°C, the pressure is 3 to 10 MPa, and the time is 0.2 to 2 min;
[0030] Preferably, the premixing step comprises the step of introducing the ethylene monomer, α-olefin monomer, impurity remover and dispersant into a mixing reactor; preferably, the mixing reactor is a tubular reactor with a static mixer.
[0031] Specifically, the method for preparing the ethylene-α-olefin random copolymer further comprises the step of adding a quencher and a stabilizer to the polymerization reactant of the polymerization reaction to terminate the reaction;
[0032] Preferably, the quencher comprises water or a C1-C15 long-chain alcohol; preferably water or a C1-C15 long-chain fatty alcohol; preferably at least one of water, undecanol or dodecanol; preferably, the quencher is added in an amount of 1 to 40 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer;
[0033] Preferably, the stabilizer comprises at least one of an antioxidant, an anti-aging agent or a stearate; preferably, the stabilizer is added in an amount of 5 to 50 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer;
[0034] Preferably, the termination reaction temperature is 120-220°C, the pressure is 3-10 MPa, and the time is 0.5-5 min;
[0035] Preferably, the termination reaction comprises the step of introducing the polymerization reactants, quencher and stabilizer into a termination reactor; preferably, the termination reactor is a tank reactor with a stirrer.
[0036] Specifically, the method for preparing the ethylene-α-olefin random copolymer further comprises the step of collecting the polymer after the termination reaction for post-treatment;
[0037] Preferably, the post-treatment step comprises the step of separating unreacted ethylene, α-olefin and light components of the dispersant from the polymer by flash distillation under reduced pressure, and the step of collecting heavy components of the polymer melt and obtaining polymer particles by extrusion and pelletization;
[0038] Preferably, the post-processing step further comprises the step of recycling the separated unreacted ethylene, α-olefin and dispersant light component as raw materials.
[0039] The invention also discloses the application of the ethylene-α-olefin random copolymer or the ethylene-α-olefin random copolymer prepared by the method in the field of photovoltaic encapsulation, especially in the application of preparing photovoltaic encapsulation adhesive film.
[0040] In some embodiments, the specific process of applying the ethylene-α-olefin random copolymer to the field of photovoltaic encapsulation film can be a conventional operation in the field. For example, the ethylene-α-olefin random copolymer can be mixed with an auxiliary agent to form a photovoltaic encapsulation film composition, and then the composition is prepared into a photovoltaic encapsulation film by a conventional processing technology in the field. Among them, the auxiliary agent can be a common auxiliary agent type in the field, for example, a cross-linking agent, a cross-linking auxiliary agent, an antioxidant, and the like.
[0041] The ethylene-α-olefin random copolymer of the present invention provides a random copolymer composed of ethylene and α-olefin, especially α-olefin with 3 to 8 carbon atoms, wherein the elution temperature range of the copolymer during the gradient temperature rising elution process is 25 to 40° C. and 45 to 120° C., wherein the molar proportion of the eluted component in the temperature range of 25 to 40° C. is 0.5 to 5%. The copolymer can be used in the field of photovoltaic film applications and has improved cross-linking and electrical insulation properties.
[0042] The ethylene-α-olefin random copolymer of the present invention contains only two components with elution temperature ranges of 25-40°C and 45-120°C after classification by a gradient temperature rising elution system, and the proportion of the eluting component in the low temperature range is low, and the polymer composition is uniform. The polymer has improved cross-linking and electrical insulation properties, and has the characteristics of fast cross-linking speed and excellent anti-induced potential decay (PID) performance when used in the field of photovoltaic film applications.
[0043] The preparation method of the ethylene-α-olefin random copolymer of the present invention can prepare an olefin copolymer with a low proportion of leaching components in the low-temperature range and uniform two-component composition based on the raw material optimization and ratio of the entire specific system. The copolymer has a fast crosslinking speed and excellent anti-PID performance when used as a photovoltaic film. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0045] Figure 1 This is the elution composition distribution result of the copolymer described in Example 5. DETAILED DESCRIPTION
[0046] The present invention provides an ethylene-α-olefin random copolymer with improved crosslinking and electrical insulation properties that can be used in the field of photovoltaic adhesive films. The ethylene-α-olefin random copolymer comprises:
[0047] (1) a soluble fraction having an elution temperature range of 25 to 40°C during a gradient elution with 1,2,4-trichlorobenzene; and
[0048] (2) a soluble fraction having an elution temperature range of 45 to 120°C during a gradient elution with 1,2,4-trichlorobenzene;
[0049] The mass proportion of the soluble fraction at 25-40° C. is 0.5-5wt%.
[0050] Specifically, the ethylene-α-olefin random copolymer, the polymerization raw materials of the ethylene-α-olefin random copolymer include α-olefin monomers and ethylene monomers; wherein,
[0051] As an implementable solution, the mass content of the α-olefin monomer is 20 to 45 wt% based on the mass of the ethylene-α-olefin random copolymer;
[0052] As an implementable solution, based on the mass of the ethylene-α-olefin random copolymer, the mass content of the ethylene monomer is 55 to 80 wt%;
[0053] As an implementable solution, the α-olefin monomer includes at least one of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene or 1-octene.
[0054] Specifically, the ethylene-α-olefin random copolymer described in the present application has a melt flow rate of 0.5 to 30 g / 10 min (2.16 kg, 190° C.) and a density of 0.860 to 0.910 g / cm 3 .
[0055] The present invention also provides a method for preparing the ethylene-α-olefin random copolymer, which comprises the steps of subjecting ethylene monomer, α-olefin monomer, impurity remover, dispersant and polymerization catalyst to polymerization reaction.
[0056] As an exemplary embodiment, the amount of ethylene monomer added is 5 to 20 wt % based on the total amount of raw material feed of the ethylene-α-olefin random copolymer. For example, the amount of ethylene monomer added is controlled to be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 wt %, etc., or any range between the above values.
[0057] As an exemplary embodiment, the amount of the α-olefin monomer added is 10 to 35 wt % based on the total amount of raw material feed of the ethylene-α-olefin random copolymer. For example, the amount of the α-olefin monomer added is controlled to be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35 wt %, etc., or any range between the above values.
[0058] The impurity remover includes at least one of alkyl aluminum or alkyl aluminoxane; preferably at least one of alkyl aluminum, methyl aluminoxane or modified methyl aluminoxane, preferably triisobutyl aluminum or octyl modified methyl aluminoxane. Preferably, the amount of the impurity remover added is 5 to 90 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer. For example, the amount of the impurity remover added is adjusted to 5, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90 ppm, etc., or any range between the above values.
[0059] As an exemplary embodiment, the dispersant includes at least one of C6-C10 aliphatic hydrocarbons, such as C6-C10 straight-chain alkanes, C6-C10 isoalkanes, C6-C10 cycloalkanes, preferably at least one of C6, C7, C8, C9 or C10 isoalkanes, for example, one or more of n-hexane, cyclohexane, methylcyclohexane, n-heptane, isoheptane, n-octane, isooctane, n-decane, toluene and xylene. Preferably, the dispersant is added in an amount of 55-80 wt % based on the total amount of raw material feed of the ethylene-α-olefin random copolymer. For example, the amount of the dispersant added is adjusted to 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80wt%, etc., or any range between the above values.
[0060] As an implementable solution, the polymerization catalyst includes a main catalyst and a co-catalyst.
[0061] As an exemplary embodiment, the catalyst includes a Group IVB-IIB transition metal compound, preferably bis(methylcyclopentadienyl)zirconium dichloride, bis(cyclopentadienyl)dimethylzirconium, disylbis(2-methylindenyl)zirconium dichloride, disylbis(N-tert-butylamino)(cyclopentadienyl)titanium dichloride, disylbis(N-tert-butylamino)(tetramethylcyclopentadienyl)titanium dimethyl, disylbis(N-tert-butylamino)(2,7-di-tert-butylfluorenyl)titanium dichloride, disylbis(N-tert-butylamino)(3-pyrrolylindenyl)titanium dichloride, dibenzhydryl(cyclopentadienyl)(9 One or more of diphenylmethylene (cyclopentadienyl) (2,7-di-tert-butylfluorenyl) zirconium dichloride, diphenylmethylene (cyclopentadienyl) (dibenzofluorenyl) zirconium dichloride, diphenylmethylene (cyclopentadienyl) (2-dimethylamino-fluorenyl) zirconium dichloride, diphenylmethylene (cyclopentadienyl) (octamethyloctahydrobenzofluorenyl) zirconium dichloride, bis (tetramethylcyclopentadienyl) hafnium dichloride, disilyl (9-fluorenyl) (3-tert-butylcyclopentadienyl) hafnium dichloride, diphenylsilyl (9-fluorenyl) (3-tert-butylcyclopentadienyl) hafnium dichloride. Preferably, the amount of the main catalyst added is 0.3 to 5 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer. For example, the amount of the main catalyst added is adjusted to 0.3, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 ppm, etc., or any range between the above values.
[0062] As an exemplary embodiment, the co-catalyst includes a fluorine-containing borane or a fluorine-containing borate; preferably one or more of tripentafluorophenyl borane, triphenyl carbon tetrakis (pentafluorophenyl) borate, and N,N-dimethylanilinium tetrakis (pentafluorophenyl) borate. Preferably, the amount of the co-catalyst added is 0.5 to 7 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer. For example, the amount of the co-catalyst added is adjusted to 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7 ppm, etc., or any range between the above values.
[0063] As an exemplary embodiment, the polymerization reaction has a reaction temperature of 120 to 220° C., a reaction pressure of 3 to 10 MPa, and a reaction time of 2 to 20 min.
[0064] For example, the reaction temperature of the polymerization reaction is controlled to be 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220° C., etc., or any range between the above values.
[0065] For example, the reaction pressure of the polymerization reaction is controlled to be 3, 4, 5, 6, 7, 8, 9, 10 MPa, etc., or any range between the above values.
[0066] For example, the reaction time of the polymerization reaction is controlled to be 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 min, etc., or ranges between any of the above values.
[0067] As an exemplary embodiment, the polymerization reaction comprises the step of continuously introducing the selected reaction materials into a polymerization reactor; preferably, the polymerization reactor is a stirred tank reactor or a tubular reactor with a circulation pump.
[0068] As an practicable solution, the method further comprises the step of premixing the ethylene monomer, α-olefin monomer, impurity remover and dispersant before the polymerization reaction;
[0069] Preferably, the temperature of the premixing step is -10 to 150° C., the pressure is 3 to 10 MPa, and the time is 0.2 to 2 min.
[0070] For example, the temperature of the premixing step is controlled to be -10, -5, 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150° C., etc., or ranges between any of the above values.
[0071] For example, the pressure in the premixing step is controlled to be 3, 4, 5, 6, 7, 8, 9, 10 MPa, etc., or any range between the above values.
[0072] For example, the time of the premixing step is controlled to be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 min, etc., or ranges between any of the above values.
[0073] As an exemplary embodiment, the premixing step includes the step of introducing the ethylene monomer, α-olefin monomer, impurity remover and dispersant into a mixing reactor; preferably, the mixing reactor is a tubular reactor with a static mixer.
[0074] As an implementable solution, the method further comprises the step of adding a quencher and a stabilizer to the polymerization reactant of the polymerization reaction to terminate the reaction;
[0075] As an exemplary embodiment, the quencher includes water or a C1-C15 long-chain alcohol; preferably water or a C1-C15 long-chain fatty alcohol; preferably at least one of water, undecanol or dodecanol; for example, conventional alcohol reagents such as water, 1-undecanol, 2-undecanol, 1-dodecanol, and 2-dodecanol. Preferably, the amount of the quencher added is 1 to 40 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer. For example, the amount of the quencher added is adjusted to 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 ppm, etc., or any range between the above values.
[0076] Preferably, the stabilizer includes at least one of an antioxidant, an anti-aging agent or a stearate, for example, antioxidant 168, antioxidant CA, antioxidant DNP, zinc stearate, calcium stearate, and magnesium stearate are all stabilizers with good performance. Preferably, the stabilizer is added in an amount of 5 to 50 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer. 48,49, 50 ppm or the like, or a range between any of the above values.
[0077] As an implementable solution, the temperature of the inactivation reaction is 120-220° C., the pressure is 3-10 MPa, and the time is 0.5-5 min.
[0078] For example, the reaction temperature of the inactivation reaction is controlled to be 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220° C., etc., or any range between the above values.
[0079] For example, the reaction pressure of the inactivation reaction is controlled to be 3, 4, 5, 6, 7, 8, 9, 10 MPa, etc., or any range between the above values.
[0080] For example, the reaction time of the inactivation reaction is controlled to be 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 2.0, 2.2, 2.5, 2.8, 3.0, 3.2, 3.5, 3.8, 4.0, 4.2, 4.5, 4.8, 5.0 min, etc., or ranges between any of the above values.
[0081] As an exemplary embodiment, the termination reaction includes the step of introducing the polymerization reactants and the quencher into a termination reactor; preferably, the termination reactor is a tank reactor with a stirrer.
[0082] As an practicable solution, the method for preparing the ethylene-α-olefin random copolymer further comprises the step of collecting the polymer after the termination reaction for post-treatment;
[0083] As an exemplary embodiment, the post-treatment step includes the steps of separating unreacted ethylene, α-olefin and dispersant light components from the polymer by flash distillation, and collecting heavy components of the polymer melt to obtain polymer particles by extrusion and pelletization.
[0084] The present invention is further described below by way of examples, but the present invention is not limited to these examples.
[0085] In the following examples of the present invention, sources and specifications of some raw materials involved are shown in Tables 1-2 below.
[0086] Table 1 Some raw material information
[0087]
[0088]
[0089] Table 2 Catalyst types
[0090] Catalyst No. Catalyst name A Disylsilylbis(2-methylindenyl)zirconium dichloride B Dimethylsilyl(N-tert-butylamino)(2,7-di-tert-butylfluorenyl)titanium dichloride C Dimethylsilyl(N-tert-butylamino)(tetramethylcyclopentadienyl)titanium dimethyl D Dimethylsilyl(N-tert-butylamino)(3-pyrrolylindenyl)titanium dichloride E Dimethylsilyl(N-tert-butylamino)(cyclopentadienyl)titanium dichloride F Benzhydryl(cyclopentadienyl)(9-fluorenyl)zirconium dichloride G Dibenzhydryl(cyclopentadienyl)(octamethyloctahydrobenzofluorenyl)zirconium dichloride H Disilyl(9-fluorenyl)(3-tert-butylcyclopentadienyl)hafnium dichloride I Diphenylsilyl(9-fluorenyl)(3-tert-butylcyclopentadienyl)hafnium dichloride J Dibenzhydryl(cyclopentadienyl)(dibenzofluorenyl)zirconium dichloride a trispentafluorophenylborane b Triphenylcarbon tetrakis(pentafluorophenyl)borate c N,N-Dimethylanilinium tetrakis(pentafluorophenyl)borate
[0091] In the following embodiments of the present invention, the polymerization method of the ethylene-α-olefin random copolymer is carried out by continuous solution polymerization in a high-pressure stirred reactor with PLC control.
[0092] After the ethylene, α-olefin, impurity remover and dispersant after dehydration and deoxygenation purification treatment are fully mixed, they are continuously fed into a 2.0-liter reactor equipped with a jacket and an internal thermocouple for temperature control, wherein the ethylene feed amount is measured by a gas mass flow controller, and the α-olefin, impurity remover and dispersant are controlled by a diaphragm metering pump to control the flow rate and flow rate. Before entering the reactor, a heat exchanger is used to control the temperature of the ethylene, α-olefin, impurity remover and dispersant solution, and added to the bottom of the reactor. Separately, the main catalyst and the co-catalyst are prepared into a solution with a dispersant, and enter the bottom of the reactor separately through a diaphragm metering pump. The quencher and the stabilizer are respectively prepared into solutions with a dispersant, and enter the bottom of the termination reactor separately through a diaphragm metering pump. The temperature of the polymerization reaction is stably controlled by the feed temperature and the jacket temperature of the reactor. The reactor is controlled to operate with full liquid at a stirring speed of 500-1000rpm. The reaction liquid flows out through the outlet pipeline at the top of the reactor, enters the termination reactor for mixed reaction with the quencher and stabilizer, and then enters the heat exchanger to be heated to 260°C. The reactor pressure (3.5MPa) is controlled by the heat exchanger outlet pressure regulating valve. The high-temperature reaction liquid is depressurized by the pressure control valve and then enters the three-stage low-pressure flash evaporation system in sequence. The small amount of ethylene removed is discharged, the α-olefin and the solvent are recycled, and the polymer melt is extruded and pelletized to obtain polymer particles.
[0093] In the following embodiments of the present invention, the polymerization raw material selection, ratio and reaction condition control parameters involved are shown in Table 3.
[0094] Table 3 Continuous polymerization conditions of the embodiment scheme
[0095]
[0096]
[0097] Comparative Example 1
[0098] The raw material system and preparation method of the ethylene-α-olefin random copolymer in this comparative example are the same as those in Example 1, except that the quenching agent is not added.
[0099] Comparative Example 2
[0100] The raw material system and preparation method of the ethylene-α-olefin random copolymer in this comparative example are the same as those in Example 1, except that the stabilizer is not added.
[0101] Comparative Example 3
[0102] The raw material system and preparation method of the ethylene-α-olefin random copolymer in this comparative example are the same as those in Example 1, except that the quencher and stabilizer are not added.
[0103] Experimental example
[0104] 1. Reactivity
[0105] This experimental example determines the polymerization activity of the reaction based on the above-mentioned embodiment and comparative example scheme respectively. The calculation method is the ratio of the weight of the dry polymer product obtained by the polymerization reaction to the molar number of the transition metal compound (catalyst) added during the reaction process. The results are recorded in Table 4 below.
[0106] Table 4 Polymerization activity results
[0107]
[0108]
[0109] It can be seen that the activity of the polymerization reaction described in the present invention is relatively suitable.
[0110] 2. Polymer composition
[0111] The copolymer prepared in Example 5 was taken and the polymer soluble fraction (SF) was subjected to a gradient temperature rise elution system, with 1,2,4-trichlorobenzene as the mobile phase, the elution temperature was 10-150°C, the heating rate was 5°C / min, and the elution composition distribution was detected and analyzed. The results are shown in the attached Figure 1 .
[0112] It can be seen that the ethylene-α-olefin random copolymer of the present invention only contains two components with elution temperature ranges of 25-40°C and 45-120°C, and the proportion of the eluting component in the low temperature range is low, and the polymer composition is uniform.
[0113] The composition distribution results of other embodiments of the present invention are similar. After classification by the gradient temperature rising elution system, only two components with elution temperature ranges of 25-40°C and 50-120°C are included, and the proportion of elution components in the low temperature range is low.
[0114] 3. Polymer properties
[0115] In this experimental example, the processing properties of the ethylene-α-olefin random copolymers prepared in the above-mentioned embodiment and comparative example were tested.
[0116] (1) The polymer soluble fraction (SF) was prepared by a gradient temperature elution system with 1,2,4-trichlorobenzene as the mobile phase, an elution temperature of 10-150°C, and a heating rate of 5°C / min.
[0117] (2) Polymer melt index (MFR) is measured using a melt indexer (MI-4). Under the test conditions of 190°C and 2.16 kg load, the weight of the molten polymer extruded through a die with a length of 8 mm and an inner diameter of 2.095 mm for a specified time is the MFR, expressed in g / 10 min.
[0118] (3) The polymer density is tested using a densitometer (immersion method METTLER). The mass of the sample suspended by a metal wire with a diameter not greater than 0.5 mm is weighed in air. The mass of the sample is not greater than 10 g, accurate to 0.1 mg, and the mass of the sample is recorded. The sample suspended by a thin metal wire is immersed in a beaker filled with immersion liquid placed on a fixed bracket. The temperature of the immersion liquid should be 23°C ± 2°C. Use a thin metal wire to remove bubbles adhering to the sample. Weigh the mass of the sample in the immersion liquid, accurate to 0.1 mg.
[0119] In this experimental example, the above processing performance test results are shown in Table 5 below.
[0120] Table 5 Copolymer performance indicators
[0121]
[0122] It can be seen that during the polymerization reaction, the addition of the quencher can terminate the reaction in time, thereby ensuring that the polymerization reaction is carried out under a relatively constant ethylene / α-olefin reaction raw material ratio, and reducing the low molecular weight low-temperature eluting components generated under the reaction conditions where the concentration of ethylene monomer is lower than that of α-olefin monomer in the later stage of the reaction.
[0123] In addition, the addition of stabilizers can effectively prevent the high molecular weight high temperature leaching components in the polymer from being degraded into low molecular weight low temperature leaching components in the subsequent high temperature post-treatment process. The combined effect of the two ensures that the low temperature leaching components in the polymer product composition account for a low proportion and maintains a good light transmittance.
[0124] Therefore, compared with the comparative example, the ethylene-α-olefin random copolymer prepared in the embodiment of the present invention has a lower content of eluting components in the low temperature range, and a higher starting temperature value in the eluting temperature range. The PID attenuation is less in 96h when applied to the photovoltaic film, and the cross-linking degree is higher under the same conditions.
[0125] 4. Copolymer film
[0126] This experimental example is based on the copolymers prepared in the above embodiments and comparative examples, and the film properties are tested after film formation.
[0127] The anti-PID attenuation performance test uses a power test environment chamber. First, the copolymer particles and diisopropylbenzene peroxide are mixed, and processed into a photovoltaic film with a thickness of 500-700μm by a cast machine. Then, it is pressed by a laminator under negative pressure conditions at 70℃ for 5min. The prepared double-glass photovoltaic modules are taken for anti-PID performance test under 96h-85℃ / 85RH / -1500V conditions.
[0128] Crosslinking degree: Using the xylene soluble test method, the copolymer particles and dicumyl peroxide are first mixed, and processed into a photovoltaic film with a thickness of 500-700 μm by a casting machine. Then, it is pressed by a laminator under negative pressure at 70°C for 5 minutes. Finally, the crosslinked photovoltaic film is taken to test the crosslinking degree and peel strength.
[0129] Light transmittance: Tested by projection spectrometer, take a clean film sample on a transparent substrate, and use the spectrometer to automatically scan and record the projection spectrum to calculate the transmittance percentage at different wavelengths.
[0130] In this experimental example, the test results of the copolymer film are shown in Table 6 below.
[0131] Table 6 Copolymer film properties
[0132]
[0133] It can be seen that the ethylene-α-olefin random copolymer of the present invention is used in the field of photovoltaic adhesive films, and has the advantage of a high degree of crosslinking while maintaining high light transmittance.
[0134] In summary, the ethylene-α-olefin random copolymer of the present invention has improved crosslinking and electrical insulation properties, and has excellent properties of fast crosslinking speed and excellent resistance to induced potential decay (PID) when used in the field of photovoltaic film applications.
[0135] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. An ethylene-α-olefin random copolymer, characterized in that: The ethylene-α-olefin random copolymer comprises: (1) a soluble fraction having an elution temperature range of 25 to 40°C during a gradient elution with 1,2,4-trichlorobenzene; and (2) a soluble fraction having an elution temperature range of 45 to 120°C during a gradient elution with 1,2,4-trichlorobenzene; The mass proportion of the soluble fraction at 25-40° C. is 0.5-5wt%.
2. The ethylene-α-olefin random copolymer according to claim 1, characterized in that: The polymerization raw materials of the ethylene-α-olefin random copolymer include α-olefin monomers and ethylene monomers; wherein, The mass content of the α-olefin monomer based on the ethylene-α-olefin random copolymer is 20 to 45 wt%; The mass content of the ethylene monomer based on the ethylene-α-olefin random copolymer is 55 to 80 wt%; Preferably, the α-olefin monomer includes an α-olefin having 3 to 8 carbon atoms, preferably at least one of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene or 1-octene.
3. The ethylene-α-olefin random copolymer according to claim 1 or 2, characterized in that: The melt flow rate of the ethylene-α-olefin random copolymer is 0.5-30 g / 10 min (2.16 kg, 190° C.), and the density is 0.860-0.910 g / cm 3 .
4. A method for preparing the ethylene-α-olefin random copolymer according to any one of claims 1 to 3, characterized in that: The method comprises the steps of subjecting ethylene monomer, alpha-olefin monomer, impurity remover, dispersant and polymerization catalyst to polymerization reaction.
5. The method for preparing the ethylene-α-olefin random copolymer according to claim 4, characterized in that: The amount of the ethylene monomer added is 5 to 20 wt % based on the total amount of the raw material feed of the ethylene-α-olefin random copolymer; and / or, The amount of the α-olefin monomer added is 10 to 35 wt % based on the total amount of raw material feed of the ethylene-α-olefin random copolymer; and / or, The impurity remover comprises at least one of alkyl aluminum or alkyl aluminoxane; preferably at least one of alkyl aluminum, methyl aluminoxane or modified methyl aluminoxane; preferably triisobutyl aluminum or n-octyl modified methyl aluminoxane; preferably, the amount of the impurity remover added is 5 to 90 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer; and / or, The dispersant comprises at least one of C6-C10 aliphatic hydrocarbons, preferably at least one of C6, C7, C8, C9 or C10 isoparaffins; preferably, the amount of the dispersant added is 55-80 wt% based on the total amount of the raw material feed of the ethylene-α-olefin random copolymer; and / or, The polymerization catalyst comprises a main catalyst and a co-catalyst; Preferably, the main catalyst comprises a transition metal compound of Group IVB-IIB, preferably bis(methylcyclopentadiene)zirconium dichloride, bis(cyclopentadiene)dimethyl zirconium, disylbis(2-methylindenyl)zirconium dichloride, disylbis(N-tert-butylamino)(cyclopentadienyl)titanium dichloride, disylbis(N-tert-butylamino)(tetramethylcyclopentadienyl)titanium dimethyl, disylbis(N-tert-butylamino)(2,7-di-tert-butylfluorenyl)titanium dichloride, disylbis(N-tert-butylamino)(3-pyrrolylindenyl)titanium dichloride, dibenzhydryl(cyclopentadienyl)(9-fluorenyl)zirconium dichloride, dibenzhydryl(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)titanium dichloride, One or more of dimethylbenzhydryl (cyclopentadienyl) zirconium dichloride, dimethylbenzhydryl (cyclopentadienyl) (dibenzofluorenyl) zirconium dichloride, dimethylbenzhydryl (cyclopentadienyl) (2-dimethylamino-fluorenyl) zirconium dichloride, dimethylbenzhydryl (cyclopentadienyl) (octamethyloctahydrobenzofluorenyl) zirconium dichloride, bis (tetramethylcyclopentadienyl) hafnium dichloride, disilyl (9-fluorenyl) (3-tert-butylcyclopentadienyl) hafnium dichloride, diphenylsilyl (9-fluorenyl) (3-tert-butylcyclopentadienyl) hafnium dichloride; preferably, the amount of the main catalyst added is 0.3 to 5 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer; and / or, Preferably, the co-catalyst comprises a fluorine-containing borane or a fluorine-containing borate; preferably one or more of tripentafluorophenyl borane, triphenylcarbon tetrakis(pentafluorophenyl)borate, and N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate; preferably, the co-catalyst is added in an amount of 0.5 to 7 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer.
6. The method for preparing the ethylene-α-olefin random copolymer according to claim 4 or 5, characterized in that: The reaction temperature of the polymerization reaction is 120-220°C, the reaction pressure is 3-10MPa, and the reaction time is 2-20min; Preferably, the polymerization reaction comprises the step of continuously introducing the selected reaction materials into a polymerization reactor; preferably, the polymerization reactor is a stirred tank reactor or a tubular reactor with a circulation pump.
7. The method for preparing the ethylene-α-olefin random copolymer according to any one of claims 4 to 6, characterized in that: The method further comprises the step of premixing the ethylene monomer, α-olefin monomer, impurity remover and dispersant before the polymerization reaction; Preferably, the temperature of the premixing step is -10 to 150°C, the pressure is 3 to 10 MPa, and the time is 0.2 to 2 min; Preferably, the premixing step comprises the step of introducing the ethylene monomer, α-olefin monomer, impurity remover and dispersant into a mixing reactor; preferably, the mixing reactor is a tubular reactor with a static mixer.
8. The method for preparing the ethylene-α-olefin random copolymer according to any one of claims 4 to 7, characterized in that: The method further comprises the step of adding a quencher and a stabilizer to the polymerization reactant of the polymerization reaction to terminate the reaction; Preferably, the quencher comprises water or a C1-C15 long-chain alcohol; preferably water or a C1-C15 long-chain fatty alcohol; preferably at least one of water, undecanol or dodecanol; preferably, the quencher is added in an amount of 1 to 40 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer; Preferably, the stabilizer comprises at least one of an antioxidant, an anti-aging agent or a stearate; preferably, the stabilizer is added in an amount of 5 to 50 ppm based on the total amount of raw material feed of the ethylene-α-olefin random copolymer; Preferably, the termination reaction temperature is 120-220°C, the pressure is 3-10 MPa, and the time is 0.5-5 min; Preferably, the termination reaction comprises the step of introducing the polymerization reactants, quencher and stabilizer into a termination reactor; preferably, the termination reactor is a tank reactor with a stirrer.
9. The method for preparing the ethylene-α-olefin random copolymer according to claim 8, characterized in that: The method further comprises the step of collecting the polymer after the termination reaction for post-processing; Preferably, the post-treatment step comprises the step of separating unreacted ethylene, α-olefin and light components of dispersant from the polymer by flash distillation under reduced pressure, and the step of collecting heavy components of the polymer melt and obtaining polymer particles by extrusion and pelletization; Preferably, the post-processing step further comprises the step of recycling the separated unreacted ethylene, α-olefin and dispersant light component as raw materials.
10. Use of the ethylene-α-olefin random copolymer according to any one of claims 1 to 3 or the ethylene-α-olefin random copolymer prepared by the method according to any one of claims 4 to 9 in the field of photovoltaic encapsulation, especially for preparing photovoltaic encapsulation film.
Citation Information
Patent Citations
Polyolefin elastomer and application thereof in photovoltaic packaging film
CN116789883A
Ethylene / alpha-olefin random copolymer for photovoltaic adhesive film and application of ethylene / alpha-olefin random copolymer
CN117567961A
Improved solution polymerization method
CN118184847A
Cited By
Method for continuous polymerization of ethylene and alpha-olefin
CN121495024A